Avaliação de variedades de lichia visando a fontes de resistência ao ácaro Aceria litchii - Arantes, Renan Fiacadori [UNESP]; De Andrade, Daniel Junior [UNESP]; Amaral, Ingrid [UNESP]; Martins, Antonio Baldo Geraldo [UNESP] (FapUNIFESP (SciELO), 2017)
Since the first report of Aceria litchi in Brazil, litchi productivity is reducing in the main productive regions. The aims of this study were to evaluate litchi varieties in relation to feeding by A. litchi mite and to determine the moisture and reducing sugars contents, seeking sources resistant to this mite. The experiment was conducted in the Fruit Growing Active Germoplasm Bank, Laboratory of Acarology and Laboratory of Soil Biochemistry at FCAV/UNESP. The plant varieties evaluated were Americana, Bengal, Groff, Mauritius and Sweet Clift varieties. Descriptions were performed regarding symptoms caused by A. litchii, moisture and reducing sugars contents present in the leaves of plant varieties. There were differences among varieties with respect to the symptoms caused by A. litchi regarding erinose formation and coloring. The final erinose formed in ‘Groff’, ‘Americana’ and ‘Bengal’ varieties is similar in relation to color and density of erineos. The highest reducing sugars and moisture contents were observed in ‘Bengal’, while the lowest values were found in ‘Mauritius’. Visually in the field, ‘Bengal’ was highly susceptible to A. litchii and ‘Mauritius’ was the least damaged by erinose. ‘Sweet Clift’ was as susceptible to A. litchi as Bengal variety. The results are pioneer in Brazil and provide subsidies for breeding programs on litchi trees resistant to A. licthii.
Evaluation of litchi varieties seeking sources resistant to aceria litchi mite
Keywords: Erinose mite; Eriophyidae; Plant breeding; Reducing sugars